Electrodeposition assisted sol-gel process to prepare CZTS thin films. (September 2022) - Xiang, Dongmei; Zhao, Aimei; Li, Bing; Peng, Zhuo; Yuan, Yujie; Xing, Yupeng; Yao, Liyong; Bi, Jinlian; Li, Wei; Zhang, Xiaoyong
Abstract: The traditional sol-gel process usually takes a long time to form a stable Cu2 ZnSnS4 (CZTS) sol-gel solution, which increases the whole process time. In this paper, an electrodeposition assisted sol-gel process was employed to reduce the solution preparation time. Cu was electrodeposited on Mo surface and ZnSnS sol-gel was rotated on Cu surface to prepare CZTS films. The solution preparation time was reduced from 12h to 30min. The mechanism of CZTS phase formation with sol-gel method assisted by electrodeposition was studied. Cu3 SnS4 phase was formed during the electrodeposition assisted sol-gel process, while Cu2 SnS3 phase was formed when the CZTS precursor during sol-gel process. Cu content was rich at the beginning of the reaction to form Cu3 SnS4 during the electrodeposited assisted sol-gel process. CZTS films with Cu/(Zn + Sn) of 0.84 and Zn/Sn of 1.03 were prepared by sol-gel method assisted by electrodeposition. Compared with CZTS films prepared by sol-gel method, CZTS films prepared by this method have larger and more uniform grains. It is also found that the thickness of MoS2 layer was thinner than the one prepared by sol-gel method. Highlights: An electrodeposition assisted sol-gel method was employed to prepare CZTS films. The solution preparation time was reduced from overnight to 30min. The grains of CZTS films prepared by this method were larger and more uniform than the one prepared by sol-gel method. Electrodeposited Cu helped to suppress the formation of MoS2 .